Who Is The Target Market Of Digital Tourism 4.0? - Felix Goenadhi; Dedi Rianto Rahadi (FIRM Journal of Management Studies, 2020)
This study is to investigate the willingness or intention of millennials and Gen Z era because nowadays, they are the new target market and their tourism destination image to visit several places in Indonesia based YouTube account "Indonesia.Travel" about their promotional video "Wonderful Indonesia-A Visual Journey." In this video, there will be four places. The first one is Bunaken, Manado; Banyuwangi, East Java; Lombok; and Wakatobi. The paper is presenting and experimental research (pre-test and post-test) to measure intention and tourism image of destination places in Indonesia and qualitative method (with Focus Group Discussion) in the open-ended questions. There is a significant influence of post-test to tourism image of choosing a destination in Millenials, and Gen Z and also there is a significant difference between post-test and pre-test, before and after the promotional video of "Wonderful Indonesia-A Visual Journey." The Research Limitation/Implication is the subject is only Millenial, and Gen Z and this research only use accidental sampling. The practical implication in this research it is hoping that the paper will contribute to doing business about the promotional video in other places in Indonesia, or the world.